UPAYA GURU DALAM MENANGANI KESULITAN BELAJAR PADA SISWA DISLEKSIA DI KELAS 3 SDN 36 CAKRANEGARA - Devioni, Ni Putu Eka Satvika; Witono, Hari; Widiada, I Ketut (Jurnal Ilmiah PENDAS: Primary Educational Journal, 2023)
As parents of students in schools, teachers are not only required to be able to teach in class, but also must be able to provide targeted guidance to students. Teachers should be able to provide guidance or solutions to student obstacles during the learning process, one of which is dyslexia learning difficulties which are the most common types of learning difficulties encountered in the school environment. This study aims to describe the efforts made by teachers in dealing with learning difficulties in dyslexic students in Grade 3 SDN 36 Cakranegara. The method used in this study is a qualitative approach with a descriptive type. Data collection was conducted through observation and interview with homeroom teacher 3 in SDN 36 Cakranegara. Data analysis is done by Miles and Huberman techniques that include data reduction, data presentation, and conclusion. The results showed that the efforts made by teachers in dealing with dyslexic students are using peer Tutor learning methods, using Learning media, providing learning assistance, increasing student motivation by using games, and providing special treatment.